Designing for robustness: surprise, agility and improvisation in policy design. Issue 4 (2nd October 2018) - Howlett, Michael; Capano, Giliberto; Ramesh, M.
ABSTRACT: How best to deal with uncertainty and surprise in policy-making is an issue which has troubled policy studies for some time. Studies of policy uncertainty and policy failure have emphasized the need to create policies able to be improvised upon in the face of an uncertain future, meaning there is a need to design and adopt policies featuring agility, and flexibility in their components and processes. Such policies require redundant resources and capabilities and this need is in strong opposition to ideas about design which equate better designs with efficiency, implying the allocation of only the minimum amount of resources possible, and which also often emphasize routinization and the replication of standard operating procedures and programme elements in order to ensure consistency in programme delivery. While these latter designs may be appropriate in stable circumstances or where competition can provide a degree of system-level resilience, this is not true for many public sector activities where government is the sole provider of particular goods and where services and future scenarios are unknown, contested or unpredictable. As studies of crisis management and other similar situations have emphasized, in these instances robustness is needed and can be planned for. This article examines the concepts of surprise, agility and improvisation and their linkages to robustness in order to both clarify terminology and outline the organizational and managerial features of policies and policy-making which prevent, and facilitate, flexible adaptation in both policy content and processes.